The Comparison Of Qingming Festival In Bengkalis City, Riau, And In Sungailiat, Bangka - Sufianto, Agustinus; Anggastia, Nita; Hayani, Yanti (Bina Nusantara University, 2012)
Qingming Festival is a great festival and tradition for Chinese to commemorate theirÂ ancestors. This activity is considered necessary to do by Chinese nation. Qingming festival reflectsÂ xiaoxin (åå¿ƒ) which means devotion toward the elderly or ancestor and is regarded as anÂ educational culture. This tradition is well preserved until now. This study is objected to compare theÂ Qingming festival held in Bengkalis City, Riau, and one held in Sungailiat, Bangka. By visitingÂ directly those places and interviewing some Chinese people there, we will study and conclude someÂ comparison on this subject.